2004
DOI: 10.1021/jf049762u
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Bisphenol A Metabolites Produced by CD1 Mice Liver Microsomes and S9 Fractions

Abstract: Bisphenol A [2,2-bis(4-hydroxyphenyl)propane] (BPA) is a widely used industrial chemical resulting in occupational and consumer exposure. BPA possesses weak estrogenomimetic activity and can be cytotoxic, though the underlying mechanisms of its toxicity toward cells are not completely understood. The metabolism of BPA by CD1 mice liver microsomal and S9 fractions was investigated. Nine metabolites were isolated and characterized using HPLC and mass spectrometry. Many of these metabolites were characterized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 37 publications
3
37
0
2
Order By: Relevance
“…In the present study, BPF-OH was neither cytotoxic nor genotoxic when HepG2 cells were exposed up to the concentration of 10 −7 M. Ortho-Hydroxylated-BPA (catechol-BPA) is a metabolite of BPA formed in mice liver microsomes (Jaeg et al, 2004) but also in vivo (Zalko et al, 2003). Catechol-BPA exhibits a high cytoxicity on freshly isolated rat hepatocytes .…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, BPF-OH was neither cytotoxic nor genotoxic when HepG2 cells were exposed up to the concentration of 10 −7 M. Ortho-Hydroxylated-BPA (catechol-BPA) is a metabolite of BPA formed in mice liver microsomes (Jaeg et al, 2004) but also in vivo (Zalko et al, 2003). Catechol-BPA exhibits a high cytoxicity on freshly isolated rat hepatocytes .…”
Section: Discussionmentioning
confidence: 53%
“…Additional details of this study are included in Section 2.1.2.2. Jaeg et al (2004) reported metabolites observed following incubation of CD-1 mouse liver microsomes or S9 fractions with bisphenol A at 20-500 mM [4.6-114 mg/L]. The metabolites included isopropyl-hydroxyphenol, bisphenol A glutathione conjugate, glutythionylphenol, glutathionyl 4-isopropylphenol, 2,2-bis-(4-hydroxyphenyl)1-propanol, 5-hydroxy bisphenol A, and bisphenol A dimers.…”
Section: Experimental Animalmentioning
confidence: 99%
“…Ionization mechanisms taking place in the ion source were investigated in the latter case and were similar to those previously reported for related structures [23]. Other applications involved the analysis of common antioxidants, slip agents and light stabilizers by SFC/APCI/MS [17] and HPLC/APCI/MS [15,19]. A few applications in the field also deal with the characterization of additives and their degradation pathways [20,21,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 63%
“…So far, ESI and APCI have been the methods of choice for additive analysis [13][14][15][16][17][18][19][20][21]. Brominated flame retardants, used in a variety of consumer and industrial products, have been successfully analyzed by HPLC/ESI/MS in biological fluids [16] and tissue samples [13,14].…”
Section: Introductionmentioning
confidence: 99%